A Comparison of Qiyas-Based Zakat al-Fitr Nominals: A Study of BAZNAS Policies across 27 Regencies/Cities in West Java (2021–2025) - Oneng Nurul Bariyah; Dita Kharisma; Yahaya Niwae (AL-IKTISAB: Journal of Islamic Economic Law, 2026)
This article analyses the practice of qiyas in determining the standard amount of zakat al-fitr in Indonesia, focusing on West Java Province during the period 2021–2025. The study examines the role of the West Java Provincial National Zakat Agency in converting zakat al-fitr obligations from staple foodstuffs, particularly rice, into monetary form, as well as the implications of applying qiyas to variations in the nominal value of zakat al-fitr across regencies and cities. This research employs a literature review method using primary sources consisting of printed and electronic literature on qiyas in ushul fiqh, provisions of zakat al-fitr within fiqh al-zakat, and Circular Letters issued by the West Java Provincial BAZNAS regarding zakat al-fitr standards. Secondary sources include books, peer-reviewed journal articles, policy documents, and other relevant references that support the analysis. Data were analysed qualitatively using a comparative approach by examining the application of qiyas in determining zakat al-fitr standards in several regions in West Java. This approach enabled the identification of differences in nominal zakat al-fitr amounts while also analysing local economic factors underlying these variations. The findings indicate that the West Java Provincial BAZNAS determines the conversion of zakat al-fitr into monetary form based on local rice prices in each region. This practice reflects the application of qiyas through an ‘illat derived from the consumption value of staple foods within local communities. Consequently, the amount of zakat al-fitr is strongly influenced by local economic and fiscal conditions, resulting in diverse zakat al-fitr standards across regions. During the study period, the lowest zakat al-fitr amount was recorded at Rp25,000 in 2021, while the highest reached Rp62,000 in 2023 in Cianjur Regency. The novelty of this study that the application of qiyas based on local price considerations produces varied zakat al-fitr standards, while highlighting the adaptability of Islamic law in responding to socio-economic dynamics.